Bromatological characterization of three agricultural wastes of interest in ruminants feeding, in Sinaloa, Mexico. Technical note - López, H. de J.; Chongo, Bertha; la O, O.; Guerra, J. E.; López, H.; Luna, Maribel (Cuban Journal of Agricultural Science, 2018)
In order to characterize the bromatological composition of three agricultural wastes: maize (Zea mays), sorghum (Sorghum sp.) and chickpea (Cicer arietinum) in Sinaloa state, Mexico, selected for their possibilities of use in ruminants feeding, was determined to the samples (n = 21) of these by-products the percentage of crude protein, neutral detergent fiber, acid detergent fiber, hemicellulose and cellular content. The crude protein, neutral detergent fiber, acid detergent fiber and cellular content showed differences (P ˂ 0.0001) between treatments, while hemicellulose was similar in the three agricultural wastes. The obtained results show that the chickpea waste has a better chemical composition than the rest. They also suggest performing physiological tests on ruminants to determine the inclusion levels and potential use of wastes, in order to determine their nutritional value. Key words: chemical composition, harvest wastes, maize, sorghum, chickpea